Solid Energetic Material Based on Aluminum Micropowder Modified by Microwave Radiation - Andrei Mostovshchikov; Fedor Gubarev; Pavel Chumerin; Vladimir Arkhipov; Valery Kuznetsov; Yana Dubkova (Crystals, 2022)
The paper discusses the application of pulsed microwave radiation for the modification of crystalline components of a high-energy material (HEsM). The model aluminized mixture with increased heat of combustion was studied. The mixture contained 15 wt.% aluminum micron powder, which was modified by microwave irradiation. It was found that the HEM thermogram has an exo-effect with the maximum at 364.3 °C. The use of a modified powder in the HEM composition increased the energy release during combustion by 11% from 5.6 kJ/g to 6.2 kJ/g. The reason for this effect is the increase in the reactivity of aluminum powder after microwave irradiation. In this research, we confirmed that the powders do not lose the stored energy, even as part of the HEM produced on their basis. A laser projection imaging system with brightness amplification was used to estimate the speed of combustion front propagation over the material surface. Measurement of the burning rate revealed a slight difference in the burning rates of HEMs based on irradiated and non-irradiated aluminum micropowders. This property can be demanded in practice, allowing a greater release of energy while maintaining the volume of energetic material.